Penerapan Konsep Pemasaran dalam Dakwah - Ab. Ghani, Abd. Mumin (Jurnal Usuluddin, 1997)
Some people have raised the question of whether the marketing concept is an appropriate adoption to the organization of dakwah. Nowadays, marketing is increasingly attracting the interest of non-profit organizations such as the organization of dakwah. In fact, the new marketing concept requires a careful analysis of people's wants and needs. Any such analysis will reveal that different groups of people (target groups) will have different needs. This means that the organization of dakwah must develop different uslub al-dakwah for various groups within the total population of dakwah. The article tries to examine the concept of marketing especially the market segmentation strategy and its utility for the organization of dakwah.